2002
DOI: 10.1007/pl00021005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin T: Its Role in the Diagnosis of Clinically Suspected Acute Myocarditis and Chronic Dilated Cardiomyopathy in Children

Abstract: This study was conducted to assess the use of the serum cardiac troponin T (cTnT) level as a noninvasive indicator to differentiate acute myocarditis and chronic dilated cardiomyopathy in pediatric patients. Myocarditis and dilated cardiomyopathy are clinically difficult to differentiate. Endomyocardial biopsy proved to be quite useful. However, the nature of the procedure--invasiveness, time-consuming, and limited sensitivity--caused some concerns, especially in pediatric patients. Hence, we attempted to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 0 publications
2
24
0
3
Order By: Relevance
“…However, in the case of several abnormal cardiac conditions in which cardiac muscle undergoes active necrosis (including cardiomyopathy), troponin T is released into the bloodstream and can be detected at high levels in the serum (26). We measured the resting serum troponin T levels in the dysferlin-null mice of 2 age groups (30 and 70 to 90 weeks old) ( Figure 3K).…”
Section: Figurementioning
confidence: 99%
“…However, in the case of several abnormal cardiac conditions in which cardiac muscle undergoes active necrosis (including cardiomyopathy), troponin T is released into the bloodstream and can be detected at high levels in the serum (26). We measured the resting serum troponin T levels in the dysferlin-null mice of 2 age groups (30 and 70 to 90 weeks old) ( Figure 3K).…”
Section: Figurementioning
confidence: 99%
“…Prevalence: While Tn is often raised in idiopathic DCM, several studies have shown that it is lower than in myocarditis and TnT but not hs-TnT might be useful in distinguishing these conditions [58][59][60][61] (Table 5). Patients with ischaemic cardiomyopathy have greater levels of TnI than DCM patients at hospital presentation but levels are more likely to remain elevated at 3 months in DCM.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…A number of studies have been conducted examining troponin release during myocarditis, DCM or heart failure in patients (Smith et al, 1997;Brandt et al, 2001;Imazio et al, 2008;Miller et al, 2007;Peacock et al, 2008). Troponin I and T have also been found to predict the severity of myocarditis and the short-term prognosis in children with acute and fulminant myocarditis and DCM (Soongswang et al, 2002;Al-Biltagi et al, 2010). Overall, troponin levels were found to increase in relation to the severity of myocardial inflammation or ventricular wall stress caused by remodeling (Agewall et al, 2011;Miller et al, 2007).…”
Section: Troponins I and Tmentioning
confidence: 99%